Investigation of Teachers' Attitudes Towards Sports in Turkey - Mehmet Şakir Salar; Hulusi ALP (INDONESIAN JOURNAL OF SPORT MANAGEMENT, 2021)
This research was conducted to examine the Attitudes of Teachers working in public schools towards Sports in terms of Different Variables. The data of the research were obtained from 403 teachers working in Aydın during the 2020-2021 academic year. As the data collection tool, "Attitude Scale towards Sports" made by Halil Evren Şentürk (2012) was used. Descriptive statistics and nonparametric tests were used to analyze the data. Mann Whitney U-test was used for comparisons of two groups, and Kruskal Wallis H was used for comparing more than two groups. The Cronbach's Alpha coefficient of the scale was found to be 0.97. As a result of the research, a statistically significant difference was found as a result of the analysis made between the sub-dimensions of the attitude towards sports in the variables of the teachers' Gender, Education and Branch (p <0.05). In the gender variable, it was concluded that the Attitudes of Female Teachers towards Sports were higher than male teachers in all sub-dimensions of the scale. When the Educational Status Variable is examined, it is seen that in the dimension of Interest in Sports, Graduate Teachers' Attitudes towards Sports are higher than Undergraduate teachers. In the Active Sports dimension, it is concluded that the Graduate Teachers' Attitude towards Sports scores are higher than the Undergraduate Teachers. It was concluded that Physics, Biology and Science, Turkish and Literature, History, Geography and Social, Religious Culture and Moral Knowledge, PDR and Philosophy, Mathematics and Information Technologies, Vocational Courses and Technology Design teachers were higher than their attitude scores. Physical Education and Sports Teachers' attitude scores in the dimension of Life with Sports Foreign Language Teachers (German and English), Chemistry, Physics, Biology and Science, Turkish and Literature, Religion and Moral Knowledge, PDR and Philosophy, Mathematics and Information Technologies, Vocational Courses and It is higher than the attitude scores of Technology Design teachers. The attitude scores of Physical Education and Sports Teachers in the Active Sports dimension are Foreign Language Teachers (German and English), Chemistry, Physics, Biology and Science, Turkish and Literature, History, Geography and Social, Classroom and Preschool, Special Education, Religious Culture and It is higher than Teachers of Morality, PDR and Philosophy, Mathematics, Information Technology, Vocational Courses and Technology Design. It was concluded that there was no statistically significant difference between the sub-dimensions of age, marital status, education level and attitude towards sports (p> 0.05).